Uji Aktivitas Antioksidan dan Penghambatan Tirosinase serta Uji Manfaat Gel Ekstrak Kulit Batang Taya (Nauclea subdita) terhadap Kulit - Charissa, Meiliana; Djajadisastra, Joshita; Elya, Berna (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2016)
Dayak women in Borneo treat their skin with natural ingredients, one of which is taya cortex (Nauclea subdita). Flavonoids that can be found in natural ingredients have antioxidant effect and can inhibit the activity of tyrosinase in melanogenesis process. The research objectives were to measure the antioxidant activity and the inhibition of tyrosinase of taya cortex extract, to obtain a stable formulation of taya cortex extract gel, and to determine the safety and efficacy on human skin. The method used for antioxidant activity test was DPPH method. The inhibition of tyrosinase was conducted with kojic acid as control. The safety and efficacy test were conducted to healthy women ages 35-50 with healthy and normal skin. The results show IC50 value of 568.58 µg/mL in L-tyrosine and 1374.69 µg/mL in L-DOPA for inhibiton of tyrosinase. Antioxidant activity assay of the extract shows IC50 value of 48.78 µg/mL and can be categorized as a powerful antioxidant (